Giant and reversible low field magnetocaloric effect in LiHoF4 compound. Issue 47 (23rd November 2021) - Xie, Huicai; Tian, Lu; Chen, Qi; Sun, Hao; Gao, Xinqiang; Li, Zhenxing; Mo, Zhaojun; Shen, Jun
Abstract : We provide a practical cryogenic magnetic refrigerant, polycrystalline LiHoF4, which undergoes a second-order phase transition below 2 K. The maximum magnetic entropy changes are 11 and 19 J kg −1 K −1 in field changes of 0.6 and 1.0 T, respectively. Abstract : Cryogenic refrigeration technology is gradually penetrating into increasing aspects of human life and industrial production. Magnetic refrigeration shows excellent application potential due to its high efficiency, good stability and environmental friendliness. It is important for a magnetic refrigeration system to secure a high-performance magnetocaloric material under a low applied magnetic field, which can greatly simplify the design and reduce the expense. In this study, LiHoF4, a polycrystalline compound prepared by an improved solid-state reaction method undergoes a second-order phase transition below 2 K. Meanwhile, an unexpected giant low-field magnetocaloric effect has been observed. The maximum magnetic entropy changes are 11.0 J kg −1 K −1, 19.0 J kg −1 K −1, and 25.9 J kg −1 K −1 in field changes of 0.6 T, 1.0 T, and 2.0 T, respectively. The giant and reversible low field magnetocaloric effect proves it to be one of the most practical candidates among the cryogenic magnetic refrigerants.